Dynamics in fermentation quality, bacterial community and metabolic profile during silage fermentation of late-harvested elephant grass. (14th December 2022) - Zhao, Jie; Yin, Xue-Jing; Dong, Zhi-Hao; Wang, Si-Ran; Li, Jun-Feng; Shao, Tao
Abstract: The present study aimed to evaluate the effects of delayed harvest and storage length on fermentation products, bacterial community and metabolic shifts of elephant grass silage. The late-harvested elephant grass (LG) was naturally fermented (NLG) for 1, 3, 7, 15, 30 and 60 days, respectively. After 60-day ensiling, NLG displayed homolactic fermentation with low pH value, butyric acid and ammonia nitrogen concentrations, and high lactic acid concentration and ratio of lactic acid to acetic acid. Pseudomonas, Sphingomonas and Pantoea dominated the bacterial community in LG, but Lactobacillus, Lactococcus and Pediococcus were the advantageous genera in 3-day and 60-day NLG. The correlation heatmap revealed that Acetobacter was positively related to acetic acid, ethanol, ammonia nitrogen and butyric acid concentrations. There were distinct differences in the KEGG metabolic profiles of fresh and ensiled LG. Ensiling suppressed the metabolism of amino acid, vitamins and energy, while promoted the metabolism of carbohydrate. The LG can be well-fermented without additives, but its low crude protein content should not be ignored when applied in agricultural practice. The ensiling process remarkably affected the fermentation quality, bacterial community and metabolic profiles of NLG.